Tourism 5A, Tourism Satisfaction, and Electronic Word of Mouth in a Small Island Destination - Descarten, Randy (Institut Pariwisata dan Bisnis Internasional, 2023)
Electronic Word of Mouth (EWOM) has gained popularity in academia due to its expansion in online communications, such as Websites, social media, and Blogs for travel and recreation purposes. These online activities in tourism can create an advantage for tourist destinations, especially for businesses and tourism service providers. Therefore, there is an urgent need to look into variables that could affect positive conduct on Electronic Word of Mouth among tourists. The primary purpose of this study is to determine the relationship between Tourism 5A's, Tourism Satisfaction, and conduct Electronic Word of Mouth among domestic tourists in Siargao Island, Philippines. The respondents of this study are domestic tourists. Instrumentation was utilizing a 5 Point-Likert Scale. This study utilizing SmartPLS-SEM, results revealed that among the Tourism 5A's, only the Amenities and Activities have a significant relationship to Tourist Satisfaction and could affect by 84.8 percent. On the other hand, Tourist Satisfaction affects EWOM by 65.7 percent.